Fiqh of Diffable in Theo-Antro-Juridical Perspective: Examining the Divine, Humane and Constitutional Foundation For the Fulfillment of the Rights of Disabled Group - Rohmah, Siti; Kholish, Moh. Anas; Galib, Andi Muhammad (Institut Agama Islam Yasni Bungo, 2021)
Since the past, stigma and various forms of discrimination have continued to haunt disabled groups. They become a group that is marginalized from society due to the limitations they experience. Diffable groups should be seen as part of a society that has different abilities. In Islamic doctrine, marginalization and discrimination against these disabled groups is an act that is blamed and prohibited because basically all humans have the same position before God and the only difference is the degree of holiness. Therefore, Islamic law through fiqh products must participate in legitimizing the fulfillment of rights for disabled groups from a religious perspective. This paper will examine the importance of the formulation of fiqh with disabilities as part of respecting human values ​​taught by Islam. Using the theo-anthro-juridical term, this paper will also describe the foundations in formulating the fiqh of persons with disabilities, including theological, humanist, and legal foundations.